Abhath muhakkamah: al-nitaj al-ilmi fi ta’lim al-lughah al-Arabiyyah li ghair al-natiqin biha - Ali, Asem Shehadeh Saleh (KIRKHS, IIUM, 2021)
Research book of (ICALL 2020) on scientific outcome in the field of teaching Arabic for speakers of other languages.